The effect of ZnCl2 concentration as extraction medium and sweet potato starch (Ipomoea batatas L.) addition on the characteristics of extract pandan edible film - Suryani, Chatarina Lilis; Haliza, Alief Nur; Wariyah, Chatarina; Sari, Yuli Perwita Sari (Universitas Slamet Riyadi Surakarta, 2026)
The use of edible film from natural materials in the food industry as food packaging is increasing because it is safer and can reduce exposure to microplastics. Natural materials such as pandan extract and sources of chlorophyll and antioxidants have higher added value as functional foods, but chlorophyll easily degraded. The formation of Zn-chlorophyll complexes can increase chlorophyll stability. In addition, fillers are needed; sweet potato starch can be an alternative filler, but the amount of addition is unknown. This study aims to evaluate the effect of variations in ZnCl2 concentration as an extraction medium and the addition of sweet potato starch to pandan edible film. The stages of making pandan edible film are chlorophyll extraction (ZnCl2 1000, 1250, 1500 ppm), mixing sweet potato starch (3, 4, and 5% w/v), heating, molding, and drying. This study used a Completely Randomized Design (CRD) factorial pattern. The resulting edible film was tested for tensile strength and color and analyzed for chemical water content, chlorophyll content, Zn content, and antioxidant activity. The results showed that the higher the concentration of ZnCl2 and the addition of sweet potato starch, the increased lightness, redness, and water content, but the edible film's chlorophyll content and antioxidant activity decreased. The best edible film made with 1000 ppm ZnCl2 media and the addition of 4% white sweet potato starch with the characteristics of total chlorophyll content of 228.21% db, antioxidant activity of 98.70%, Zn content of 4.33 mg/g, water content of 16.86% wb, lightness 34.92, redness -2.67, yellowness 10.37 and tensile strength 4.99 MPa. Pandanus edible film has the potential to use as biodegradable high fat food packaging.